Best management practice development to minimize environmental impact from large flow-through trout farms - MacMillan, John R.; Huddleston, Terry; Woolley, Max; Fothergill, Kent (Aquaculture, 2003)
Minimization of specific pollutants from US rainbow trout ( Oncorhynchus mykiss) farms is motivated by regulatory requirements and corporate philosophy, but success in reducing discharge of potential pollutants is dependent upon facility design, operation, and financial commitment. In south central Idaho (USA), aquaculturists are subject to a federal Clean Water Act total maximum daily load (TMDL) required reduction in effluent total phosphorus (TP) and total suspended solids (TSS). Total effluent mass loads of TP must be reduced by 40% from a baseline established in 1991. Effluent TSS limits, while not completely determined, are anticipated to need to be maintained at 3–5 mg/l. These reductions must be achieved by 2004. Until 2004, raceway effluent TP must not exceed a mean net concentration of 0.1 mg/l and TSS must not exceed 5 mg/l. Clear Springs Foods has developed a waste minimization program using practices developed over the past 12 years. These practices rely on application of a disciplined best management practices (BMP) plan, optimization of feeding practices, and use of low-phosphorus feed ingredients. Individual facility-specific BMP plans were developed using a hazard analysis critical control point (HACCP)-like approach that is the focus of this report. Corporate philosophy has embraced the importance of environmental stewardship because of its community benefit and long-term financial implications. These efforts have resulted in a 40% reduction in effluent phosphorus from measured 1990 mass loads. Fish production volumes and fish quality have been maintained and increased costs limited.